Fundamentals of Economic and Monetary Policy in Islam - Haris Maiza Putra; Ending Solehudin (AL-FALAH : Journal of Islamic Economics, 2022)
Purpose: This study aims to look at the monetary system from an Islamic perspective.Design/Method/Approach: This research is literature research using a qualitative approach and using descriptive methods related to the discussion.Findings: The results of the study indicate that it is necessary to abolish the interest system, increase investment, maximize zakat instruments, and others regarding cross-subsidies or bridges between the rich and the poor, and besides that, the central bank is obliged to assess the demand for money in the context of price stability and other monetary policy targets. Originality/Values: The main contribution of this research is to fill the gap. The majority of studies mainly focus on the conceptual and theoretical aspects of the Islamic monetary economy without any empirical validation in the field. The author suggests the application of Islamic monetary instruments to carry out the ideal goals of management-based Islamic monetary.